HUBUNGAN GAYA HIDUP DAN KEBIASAAN MAKAN DENGAN KADAR HAEMOGLOBIN (Hb) PADA ANAK JALANAN DI KOTA MEDAN - Ginta Siahaan (Poltekkes Kemenkes Medan, 2017)
According to Law No. 23 The year 2002 about child protection, the rights of the child is part of a compulsory human rights guaranteed, protected and fulfilled by parents, society, government and state.while in Article 4 paragraph 1 mentioned that the children who have no parents are entitled to by the state or the nursery or the body. This research aims to know the relationship between eating habits and Lifestyle with the level of Haemoglobin (Hb) on the Street Children in the City of Medan. This research done in some places where ordinary street children abstain as Simpang Red light Titi Kuning, Aksara, Juanda, Pringgan, Simpang Petisah and Terminal Amplas, and Pinang baris in the city of Medan. Data collection is done for 1 months starting from April 20 s/d 20 May 2013, where the location of this research are expected to represent the community of street children in the city of Medan. The type of this research is cohort studies with cross sectional design (cut bars). The population in this research is the whole street children Simpang Red light Titi Kuning, Aksara, Juanda, Pringgan, Simpang Petisah and Terminal Amplas, and Pinang baris in the city of Medan. estimated 300 people, now samples on the research is part of the population of street children based on the criteria of inclusion where one of the criteria is the street children aged 14 - 24 years. From these criteria get samples as much as 72 people. This research has been approved by the code of conduct research FK USU. Based on the results of research can be concluded that the lifestyle of street children is to have the categories less of 36 people (50%), and eating habits of street children are the most is have less category of 28 people (38.9%) while for the level of haemoglobin (Hb) street children are the most is have low category of 42 people (58%), to see the relationship between the statistical tests with Test Chi-Square, where there is a significant relationship ( p= 0.000 < 0.05 ) between lifestyle with the level of haemoglobin (Hb), whereas there is no significant relationship ( p= 0.096 > 0.05 ) between eating habits with the level of haemoglobin (Hb). The researcher recommends that for an observer of street children should perform routine counseling every month so that the street children can be exposed to about the lifestyle that hygiene, kiebiasaan eat good and orderly pentinhnya eat for street children.